Changes in Corneal Morphology and Biomechanics in Cases of Small Incision Lenticule Extraction with Prophylactic Accelerated Collagen Cross-Linking - Fei Mo; Yu Di; Ying Li (Journal of Ophthalmology)
Purpose. To study the corneal morphology and biomechanics in cases of small incision lenticule extraction with prophylactic accelerated collagen cross-linking (SMILE Xtra). Methods. This study was a retrospective study. 28 eyes of 14 patients with moderate-high risk of postoperative ectasia according to the Randleman scoring system underwent SMILE Xtra procedure. Outcome data were recorded including uncorrected distance visual acuity (UDVA), manifest refraction spherical equivalent (MRSE), surface regularity index (SRI), surface asymmetry index (SAI), simulated keratometry (SimK), posterior axial curvature (PAC), anterior and posterior corneal elevations (ACE and PCE), central corneal thickness (CCT), corneal resistance factor (CRF), corneal hysteresis (CH), and cornea-compensated intraocular pressure (IOPcc). The follow-up period was 12 months. Results. There were 28, 26, 22, 12, and 10 eyes enrolled at postoperative 1st day and 1st, 3rd, 6th, and 12th months, respectively. The UDVA improved from 1.27 ± 0.18 logMAR preoperatively to -0.06 ± 0.04 logMAR postoperatively (P<0.05). The MRSE improved from -5.05 ± 1.15 D preoperatively to -0.14 ± 0.30 D postoperatively (P<0.05). SAI, SimK, PAC, PCE, and CCT all changed significantly at 1st month postoperatively (P<0.05) and stabilized during the remainder of the follow-up (P>0.05). There was no significant change in SRI or ACE before and after surgery (P>0.05). CRF, CH, and IOPcc all decreased significantly at 1st month postoperatively (P<0.05) and remained stable afterwards (P>0.05). Conclusions. The changes in the corneal morphology and biomechanics remained stable after SMILE Xtra, and there was no sign of postoperative ectasia or refractive regression. Combined with the improvement of visual and refractive results, SMILE Xtra may be a promising method for corneal refractive surgeries in patients at risk.